An experimental study on the linear differential scattering coefficients of the Trommel Sieve Waste (TSW) - Icelli, Orhan; Boncukcuoglu, Recep (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The linear differential scattering coefficients (LDSCs) at 60 keV are measured for TSW at seven angles ranging from 60 degrees to 120 degrees at intervals of 10 degrees. The results are compared with relativistic and non-relativistic theoretical values. The purpose of this work is to seek evidence whether there is a relationship between the LDSC and the scattering angle. This is the first time the LDSCs have been measured at energies lower than 100 keV, so there is a lack of comparable findings reported in the literature. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: ATOMIC FORM-FACTORS; 59.5 KEV PHOTONS; KEV GAMMA-RAYS; CROSS-SECTIONS; COHERENT SCATTERING; ELASTIC-SCATTERING; ATTENUATION COEFFICIENTS; BORON-COMPOUNDS; Nuclear Science & Technology